Pengembangan Media Pembelajaran IPS dengan Konsep IPSAC menggunakan Powerpoint Interaktif Materi ASEAN Country - Andini Eka Putri; J. Julia; Nurdinah Hanifah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This development research is to describe the design and construction of social studies learning media at MI Al-Mu'awanah Bekasi City in anticipating the need for learning media that is easier to understand for class VI students in ASEAN Country material, the aim of creating innovative learning media using computer methods using PowerPoint interactive. This development research model uses the ADDIE procedural research model through five stages of development, namely the Analyze, Design, Development, Implementation, and Evaluation stages, the research method uses a descriptive qualitative method, the results of research in small groups get students' Posttest scores increased by 0.55 is in the range 0.3 ≤ g ≤0.70, meaning Fairly Adequate from the pretest learning results using NGain Score, media expert validation with good or appropriate criteria of 80% of the assessment degree and the validation value is quite high at 84% of the assessment degree by material experts. Validation of the questionnaire instrument in small group response assessment trials with Cronbach's Alpha, the average product validation in small group trials was 0.9623 > rtable value 0.3783, rtable on df 20 = N-2 =20-2=18, equal to 0.05=0.3783, meaning rcount valid, Cronbach'Alpha is 3714.00 > 0.70, then the test instrument is declared reliable.